STORYBOARDING: A MODEL TECHNIQUE FOR THE LANGUAGE LEARNING PROCESS - Wahid, Rizwana; Aziz, Ahtisham (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
The current paper mainly focuses on three objectives: introduces the concept of storyboard teaching, highlights its usefulness in higher education as a variant in online and offline courses or as an adapting teaching materials tool according to the learners’ needs and context of learning, and then recommends its use in the classroom especially in language and literature, mixed with other innovative teaching techniques. Moreover, the current paper focuses on how storyboarding provides platforms for the students to be active, creative, and critical thinkers and learning is not limited to only remembering while they analyze their works, reflect, and progress. The researchers have highly recommended incorporating the storyboarding technique in the higher education classrooms and fusing it with other innovative techniques to make a classroom interesting, engaging and interactive. Adding the storyboarding approach, students get motivation, feel confident and competent after the completion of mapping out their ideas visually, cognitively and creatively.